Professional and personal ethics in translation: A survey of South African translators’ translation strategies and motivations - Kruger, Haidee; Crots, Elizabeth (Stellenbosch Papers in Linguistics Plus, 2014)
The aim of the study reported on in this article was to explore South African translators’ responses to various kinds of ethically contentious material at the textual level, in the context of particular text types and hypothetical translation situations. The study made use of a survey design based primarily on closed-ended questions, administered to an availability sample of 31 South African translators drawn from the membership of the South African Translators’ Institute (SATI). The survey was, in the first instance, designed to solicit respondents’ opinions regarding which translation strategies they would most likely select to deal with particular kinds of ethical challenges. In order to better understand the factors affecting the selection of translation strategies, the impact of two translator factors (experience and age) and two text factors (text type and type of ethical problem) was investigated. In the second instance, the survey aimed to investigate why respondents selected particular strategies, and indirectly how they view their ethical responsibility. To this end, possible reasons for the selection of specific translation strategies were formulated and categorised as primarily influenced by either personal or professional ethics. In addition to this overall analysis, the study analysed differences in the role of personal and professional ethics depending on the type of ethical problem, the type of text, respondents’ age, and different levels of translation experience. The findings of the study suggest an overwhelming preference for faithful translation, but also reveal an interplay between personal and professional ethics as the motivation for this choice, with some differences across text type and kind of ethical problem. It appears that experience leads to a greater preference for both faithful translation strategies and a stronger influence of professional ethics. However, the data also suggest that age and/or generational differences may play a role in the selection of translation strategies, as well as in the effect of personal and professional ethics, with the oldest and youngest respondents in the sample more likely to opt for strategies other than faithful translation, motivated more frequently by personal rather than professional ethics.